Menertawakan Untuk Mencerahkan: Studi Analisis Humor Dalam Komunikasi Keagamaan Pada Podcast Login - Achmad Faesol, Achmad Faesol; Irma Firnanda, Irma Firnanda (Icon: Islamic Communication and Contemporary Media Studies, 2025)
This study aims to analyze the role of humor in religious communication within the Login podcast, particularly in discussions addressing sensitive interfaith issues. In this context, humor is viewed not merely as entertainment but as a communication strategy capable of easing tension, creating spaces for dialogue, and fostering a sense of togetherness. The research employs a descriptive qualitative approach using Roland Barthes’ semiotic analysis theory to examine the discourse in episode thirty. The findings reveal that humor in the Login podcast is applied in a measured and contextual manner, effectively lightening the atmosphere, serving as an educational medium, dismantling stereotypes, promoting equality, and encouraging audiences to think more critically without undermining the sacred values of religion. Such use of humor proves effective in capturing the attention of younger generations and creating a more fluid and dialogical digital public sphere. Humor as an approach in religious communication in the digital era exemplifies how religion, media, and humor can synergize to build a peaceful and enlightening narrative of religiosity.